Antecedents and Consequences of Corporate Social Responsibility in Poverty Alleviation Initiatives - Arli, Denni I.; Morrison, Pamela D. (ANIMA Indonesian Psychological Journal, 2008)
For many years, agencies and corporations have initiated programs and implemented inter- ventions to help impoverished groups but the results of these initiatives have often been quite dis- couraging. Adverse shocks such as severe health incidents or loss of employment, can happen in every household. These incidents can severely impact households, especially the poor. These impov- erished households are likely to need both economic and social restoration. Thus, corporations are in- creasingly asked to provide innovative solutions to human poverty. One solution is through Corporate Social Responsibility (CSR), and another is through Social Entrepreneurship (SE), a strategy that seeks an opportunity to satisfy some unmet needs that the state welfare system will not or cannot meet. By studying both CSR and SE, we will highlight the mechanisms, key similarities and differ- ences of these two forms of strategy and develop a framework that approaches poverty alleviation more systematically and effectively. Selama bertahun-tahun, para agensi dan korporasi telah memulai program dan implementasi intervensi untuk menolong kelompok miskin, namun hasil inisiatif itu sering mengecewakan. Peristiwa yang mengejutkan seperti gangguan kesehatan berat atau kehilangan pekerjaan, dapat ter- jadi dalam setiap rumah tangga. Kejadian tersebut dapat sangat memengaruhi rumah tangga, terutama pada orang miskin. Rumah tangga yang jatuh miskin ini membutuhkan baik pemulihan ekonomi maupun pemulihan sosial. Dengan demikian, korporasi makin dituntut menyediakan solusi inovatif terhadap kemiskinan manusia. Salah satunya adalah melalui tanggung jawab sosial perusahaan (TSP), atau melalui kewiraswastaan sosial (KS), suatu strategi yang mencari kesempatan memuaskan kebutuhan yang tak akan atau tak dapat dipenuhi oleh sistem kesejahteraan negara. Dengan mempelajari TSP dan KS, kami akan mengemukakan mekanisme, kesamaan kunci dan perbedaan kedua bentuk strategi tersebut dan mengembangkan sebuah kerangka pendekatan pengurangan kemiskinan secara lebih sistematis dan efektif.